The influence of socioeconomic factor among organized smallholder towards awareness of Malaysian sustainable palm oil / Che Ashraf Che Aszahar and Syahrizan Syahlan - Che Aszahar, Che Ashraf; Syahlan, Syahrizan (Faculty of Plantation and Agrotechnology, 2018)
Malaysia Sustainable Palm Oil (MSPO) is an organization that responsible in monitoring, controlling and evaluating economic, social and environmental impacts of the production in Malaysia. In this study, the researcher focus more on the influence of socioeconomic factor among the organized smallholders toward the awareness of MSPO. This survey is conducted based on two main objective which are to identified the factor that influence the smallholders towards the awareness of MSPO and to identify the relationship and the best dominant factor toward the awareness of MSPO. The number of population in this area is around 225 smallholders. But generally this area are divided to two types of smallholder which are independent smallholder that consists of 150 smallholders and the dependent smallholder that consists of 75 smallholders. This study is conducted only on dependent smallholders. The sample of the population for the 75 persons is only 63 sample. Thus, this survey is conducted by distributed questionnaire to the smallholders around 63 persons that are selected randomly in Seri Mendapat, Melaka. Data collected will be analyzing using the Statistical Package for Social Science (SPSS) in order to get results for descriptive analysis, factor analysis, correlation and also regression. As for regression analysis, the experience factor shows the highest coefficient among the others factor with 0.325 value. The result also shows that R² is 0.659 which indicate that 65.90% of the independent variables have been identified in this study. Hence, it can be concluded that experience has become the most dominant factor among the others factor. The others factor such as knowledge, government status and training also gave some affect to the MSPO awareness but it not highly as compared to the experience. For the recommendation, researcher should more study about the others factor that can influence the MSPO awareness.